P41 Correlation between analgesics. (17th September 2017) - Robitaille, E; Lui, K; Debouter, K; Ma, J; Carpenter, A; Reid, R
Abstract : Study Design: Pragmatic randomised controlled trial. Objectives: To determine the effect of adding analgesics to a standardised rehabilitation program following lateral ankle sprain (LAS) on long-term outcome measures. Background: Recent guidelines report strong evidence that a short course of certain analgesics may decrease pain and improve function following lateral ankle sprain (LAS). However, reports of swelling and static instability in subjects receiving non-steroidal anti-inflammatories (NSAIDs) following LAS have led to concerns of adverse healing and have been criticised for short-term follow-ups and limited outcome measures. Methods and Measures: All Canadian Armed Forces (CAF) members reporting to Garrison Petawawa with an acute grade I/II LAS were invited to participate. Eligible subjects were provided a standardised rehabilitation program and randomised to receive either; no medication or a 7 day course of: acetaminophen 500 mg four times/day, celecoxib 100 mg twice/day, or naproxen 500 mg twice/day. In order to determine a statistically significant difference between groups in the Activities of Daily Living subscale of the Foot and Ankle Abilities Measure, using a two-sided significance set at 0.05, a power of 80%, and an estimated attrition rate of 25%, 40 subjects/group were required. Secondary outcome measures included clinical measures of pain, swelling, mobility and instability at 2, 4 and 52 weeks. Results: To date, 66 subjects have been enrolled and randomised into the; no medication (n=17, 28.3±9.9 years), acetaminophen (n=17, 28.6±7.2 years), celecoxib (n=16, 51.8±14.9 years), or naproxen (n=17, 32.7±10.7 years) groups. All subjects have reported clinically relevant changes in pain and self-reported function between baseline and 3 months, without any differences static instability. Interestingly, only subjects in the no medication or acetaminophen groups have reported clinically relevant changes in swelling. Conclusion: The preliminary results of this study suggest that the concerns regarding adverse effects on healing and delayed recovery in subjects receiving NSAIDs following LAS may require reconsideration.